The Effect of Good Corporate Governance, Profit Management and Earning Per Share on Share Prices in Companies Included in the Jakarta Islamic Index for 2017-2021 - Eka Ermawati; Alex Ferdinal; Kelik Purwanto; Zurico Rayga (Greenation International Journal of Economics and Accounting, 2023)
The problem in this study is still the lack of good corporate governance implementation , whether or not the determination of earnings management in the company is effective, the increase or decrease in earnings per share from year to year is important to know whether the work done by the company is good or not, there are still many investors who buy and selling is not based on information and research purposes to analyze and study the effect of good corporate governance on stock prices, to analyze and study the effect of earnings management on stock prices, to analyze and study the effect of earnings per share on stock prices, to analyze and study the effect of good corporate governance , earnings management and earnings per share on stock prices, this research is a quantitative study. The type of data used is secondary data obtained from www.idx.co.id. Good corporate governance has no effect and is negative on the stock prices of companies included in the 2017-2021 Jakarta Islamic index, earnings management has no effect and negatively on the stock prices of companies included in the 2017-2021 Jakarta Islamic index, earnings per share has a significant effect on the stock prices of companies included in the 2017-2021 Jakarta Islamic index. The conclusion of share ownership by managerial and earnings management has not been able to improve company performance apart from managerial ownership there are still many other factors that can affect stock prices in a company which investors can also see to get consideration in investing and earning per share becomes one of the considerations for investors to invest is because earnings per share can affect stock prices and if earnings per share is high, the welfare of investors will also be higher.